Prevalence of CTX‐M resistance marker and integrons among Escherichia coli and Klebsiella pneumoniae isolates of clinical origin. (May 2016) - Shaikh, S.; Rizvi, S.M.D.; Anis, R.; Shakil, S.
Abstract: Bacterial pathogens producing CTX‐M beta‐lactamases are emerging around the world as a source of resistance to oxyimino cephalosporins such as cefotaxime. In this study, we have investigated the prevalence of bla CTX‐M genes among clinical isolates of Escherichia coli and Klebsiella pneumoniae . Of the double‐disk synergy test‐positive E. coli ( n  =   94) and Kl. pneumoniae ( n  =   73) strains isolated during the study period, 41 (44·08%) E. coli and 32 (43·24%) Kl. pneumoniae isolates were found to be positive for bla CTX‐M genes. Twenty‐two integrons (13 for E. coli and 9 for Kl. pneumoniae ) were detected whose sizes ranged from 600 bp to 1·5 kb. All these integrons were found to be of Class1 type and were invariably PCR positive for int1 and sul1 genes. Marker transfer experiments demonstrated plasmid‐mediated transfer of cefotaxime and ceftazidime resistance markers. In addition, analysis of the enterobacterial repetitive intergenic consensus (ERIC)‐PCR typing of the bla CTX‐M ‐carrying isolates showed that they were genetically diverse and heterogeneous suggesting that multiple subtypes of the species were involved in infection. Significance and Impact of the Study: A high frequency of bla CTX‐M ‐resistant marker has been found in Escherichia coli and Klebsiella pneumoniae isolates of clinical origin. Analysis of the ERIC‐PCR typing of the bla CTX‐M ‐carrying isolates showed that they were genetically diverse and heterogeneous suggesting that multiple subtypes of the species were involved in infection. Abstract : Significance and Impact of the Study: A high frequency of bla CTX‐M ‐resistant marker has been found in Escherichia coli and Klebsiella pneumoniae isolates of clinical origin. Analysis of the ERIC‐PCR typing of the bla CTX‐M ‐carrying isolates showed that they were genetically diverse and heterogeneous suggesting that multiple subtypes of the species were involved in infection.